The Relationships Between Money Cost, Investment, and the Rate of Return - Stockfisch, J. A. (Quarterly Journal of Economics, 1956)
Introduction, 295. — I. Increasing eosts and the distribution of earnings, 296. — II. Increasing costs and the rate of return, 299. — III. Implications and conclusions, 301.